Law enforcement agencies in the system of state subjects of managing financial system of Ukraine - T. A. Kobzieva (Bulletin of Kharkiv National University of Internal Affairs, 2018)
Based on the analysis of current national legislation that defines administrative and procedural status of law enforcement agencies, the author has singled out those, which are mostly engaged in law enforcement activities in the area of financial system administration. It has determined that law enforcement system must solve a number of social problems, including: slow paces of economic development; the imbalance of economic system; lag in adapting to changes in external trade and financial markets; excessive social tension, which adversely affects the reproductive process; low level of meeting the needs of an individual, etc. It has been established that the main difference between law enforcement agencies and other state structures is that law enforcement institutions specially endowed with state powers to carry out activities in protecting human and civil rights from violations under the law. It has been proved that law enforcement agencies – are special state agencies engaged in law enforcement activities aimed at protecting the rights and legitimate interests of citizens, companies and organizations, the state and society, ensuring security, law and order and legality in the country. It has been indicated that the activities of these public agencies aimed at ensuring the stability in the sphere of managing financial system, taking measures to prevent violations of the rights, freedoms and interests of stakeholders and the state in general and realizing investigation of the most dangerous among them.